The Chained Memories of Youth: A Study of Lyrical Narrative in The Songs of Siren and Rain and Snow Falls (“无法告别的青春之歌 论《赛莲之歌》与《雨雪霏霏》 ) - æ½˜èˆœæ€¡, Poon Soon Y (Journal of Chinese Literature And Culture 馬大華人文學與文化學刊, 2015)
Abstract Li Yongping and Zhang Guixing are both Mahua Borneo writers, residing in Taiwan in the late years. They are known as the "first generation of belated provincial". Both of them deal with the same interest of writing topic and their writings are tend to have highly poetic aesthetic refined language style. Moreover, the ways of narration in their writings are tend to be lyrical. Li Yongping’s youth confessions story Rain and Snow Falls, is the beginning of his writing which focus on "Borneo" while Zhang Guixing’s The Songs of Siren is also deal with youth topic of writing. Both novels respectively present a poetic youth of memories and in this case I find that both novels can form a set of relatively interesting dialogue. Consequently, this paper will firstly discuss about the "lyrical narration" of both novels while the second part and the third part will focus on the differences and similarities of the aesthetics significance of both stories, in order to figure out as well as to highlight both author’s personal feelings and historical debts of tension in literary way. 摘要 李永平和张贵兴同为马华婆罗洲作家，被称为在台湾定居的“迟来的外省第一 代”。两位小说家所处理的素材有不谋而合之处，在写作方面也都趋向具有高度 美感的精炼语言风格，是诗化般的文学创作，并趋向抒情式的叙事方式。李永平 的《雨雪霏霏》是他再次书写“婆罗洲”题材的小说，也是一本青春忏悔录，而 张贵兴的《赛莲之歌》也同样以婆罗洲书写为题材，主要叙述青春成长的故事。 两部小说各自以抒情的语调述说成长的经历与原乡的回忆，因此可见李永平和张 贵兴的青春作品足以自成一组相对有趣的对话。因此，本文拟从“抒情视野”的 角度切入，探讨两部作品中的抒情美学，并从中分析在诗化般语境下的叙事手段 为作品带来的意义。本文第一部分先解析“抒情化”的小说特质，第二部分与第 三部分则分别探讨李永平《雨雪霏霏》与张贵兴《赛莲之歌》的叙事美学与抒情 特质，并试图在抒情视野的角度上探讨两部作品的同与不同，以此凸显两位作家 对个人情怀和历史债务思考的张力。